The Significance of Place in the Novel "Zarayib Al-Abid" by the Novelist Najwa Ben Shtawan - Abdessalam, Najah Salah; Muhammad, Ahmed Bilal Al-Amin (Al-Mukhtar Journal of Social Sciences, 2026)
The Arab intellectual thought has not been devoid of this tendency - the tendency of place. With the evolution of literature, the concept of place has also become more personalized than before. The aim of the research was to define the place and its impact on narrative elements, then to trace the reverse development of the place, and finally to point out the starting point, where we find that the writer has used this technique abundantly and clearly. From the semiotics of place to the interrelation of place with narrative elements, it is a correlation that begins with the problem of breaking the bond with the specific defined place to interweaving with a number of places that disappear at times and reappear at other times according to the events, and the result is a compelling sequence of events that the reader does not anticipate.
Keywords: Najwa bin Shatwan; Semantics of place; literature